HPV Vaccine Hesitancy Among Medical Students in China: A Multicenter Survey - Zhou, Liangru; Wang, Jian; Cheng, Pengxin; Li, Yue; Liu, Guoxiang; Zhang, Xin (Frontiers in Public Health, 2022)
Background: In order to examine HPV information sources, vaccine hesitancy, and the association between the two variables. An online survey of HPV information sources and vaccine hesitancy was conducted among Chinese medical students. Methods: The World Health Organization (WHO) Vaccine Hesitancy 3C model was used to evaluate reasons for respondents' vaccine hesitancy. A probit model was used to investigate the association between vaccine information sources and vaccine hesitancy. Results: The reported rate of vaccine hesitancy was 62.36%. Convenience was the primary factor for vaccine hesitancy in medical students, and 37.23% used a single source to obtain vaccine information. A multivariate analysis revealed that men were 9% more likely to be hesitant about the HPV vaccine than women. Respondents without partners were 15% less hesitant than those with a partner. Respondents receiving HPV information through the Internet were 12% less likely to report vaccine hesitancy than those receiving information from other information channels. Conclusions: HPV vaccine hesitancy requires more attention. Future studies could examine whether increasing vaccination locations and dissemination of information about the safety and effectiveness of HPV vaccines as well as using Internet media would help reduce medical students’ vaccine hesitancy and expand HPV vaccine coverage.